Prohibition of Price Discrimination Practice Under Law No. 5 Of 1999 On Prohibition of Monopoly Practices and Unhealthy Business Competition - Hangga Prajatama (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2019)
In the business world, business competition or competence among business people in seizing the market is very reasonable. However, this becomes unnatural when the competition is carried out in an unfair manner, with the aim of preventing other business actors from competing (barrier to entry) or shutting down competitors' businesses. One form of anti unfair competition carried out by business actors in creating market power has been anticipated in Law Number 5 of 1999, namely the existence of price discrimination. The research method used is normative juridical, namely legal research that emphasizes the review of legal documents and library materials related to the subject matter. Based on the research that has been done, there is an Article that Regulates Regarding Price Discrimination in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, which is located in Article 6 which states that business actors are prohibited from making agreements that cause one buyer to pay a price that is different from the price that must be paid by other buyers for the same goods and / or services. and the Guidelines for the Business Competition Supervisory Commission on Implementation Provisions in Article 6 of Act Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.Keywords: Prohibition, Price Discrimination, Law No. 5 of 1999.